GAMBARAN TINGKAT KESADARAN PASIEN CEDERA KEPALA MENGGUNAKAN GLASGOW COMA SCALE (GCS) - Muhammad Riduansyah; Muhammad Zulfadhilah; Annisa Annisa (Persatuan Perawat Nasional Indonesia (JPPNI), 2020)
Cedera kepala merupakan kasus kegawatdaruratan yang sering dijumpai di Instalasi Gawat Darurat (IGD). Pasien membutuhkan penilaian tingkat kesadaran untuk menentukan tingkat keparahan dan cedera kepala yang dialami. Tujuan: Untuk mengetahui gambaran tingkat kesadaran pasien cedera kepala menggunakan Glasgow Coma Scale (GCS). Metode: Penelitian cross sectional ini melibatkan 30 responden yang mengalami cedera kepala dengan menggunakan metode accidental sampling. Pengumpulan data menggunakan instrumen GCS yang terdiri dari tiga komponen respons kesadaran yaitu mata, verbal dan motorik. Analisis data univariat dilakukan untuk mengetahui frekuensi dan persentase. Hasil: Mayoritas responden berjenis kelamin laki-laki (83,3%) dengan usia 36-45 tahun (53,3%) dan responden paling banyak memiliki tingkat kesadaran composmentis (30%). Respons mata terbanyak yaitu spontan (33,3%), respons verbal terbanyak yaitu orientasi baik (36,3%), dan respons motorik terbanyak yaitu mengikuti perintah (30%). Diskusi: Laki-laki lebih banyak terlibat dalam aktivitas yang berisiko tinggi sehingga kemungkinan mengalami cedera kepala lebih tinggi. Usia perlu mendapatkan perhatian, karena semakin bertambah usia ada kemungkinan semakin buruk pemulihan pasien. Pasien cedera kepala akan tetap sadar penuh jika sistem aktivasi retikuler (RAS) di batang otaknya tetap utuh atau tidak terganggu. Simpulan: Diharapkan menjadi informasi tambahan bagi rumah sakit dalam meningkatkan mutu asuhan keperawatan pada pasien cedera kepala, terutama pemantauan tingkat kesadaran. Hasil penelitian ini juga diharapkan menjadi sumber informasi dan referensi di institusi pendidikan keperawatan mengenai gambaran tingkat kesadaran pasien cedera kepala menggunakan GCS. Diperlukan penelitian lebih lanjut untuk membandingkan keakuratan penilaian tingkat kesadaran dengan GCS dan skala alernatif lainnya seperti Full Outline of Unresponsiveness (FOUR) atau Comprehensive Level of Consciousness Scale (CLOCS).Kata Kunci: Cedera kepala, GCS, tingkat kesadaran.Overview of Consciousness Level of Patients with Head Injury Using Glasgow Coma Scale (GCS)ABSTRACTHead injury is an emergency case that is often found in the Emergency Room (ER). Patients require an assessment of the consciousness level to identify the severity of the head injury. Objective: To obtain an overview of the consciousness level of patients with head injury using the Glasgow Coma Scale (GCS). Methods: This research is a cross-sectional study involving 30 respondents with head injury taken using the accidental sampling method. Data were collected using the GCS instrument, consisting of three components of awareness responses: eye, verbal, and motor. Univariate data analysis was performed to identify frequency and percentage. Results: The majority of respondents were male (83.3%) aged 36-45 years (53.3%), and most respondents had compos mentis (30%). The majority of eye response was spontaneous (33.3%), the majority of verbal response was good orientation (36.3%), and the majority of motor response was following orders (30%). Discussion: Men are more involved in high-risk activities, so that the possibility of having a head injury is higher. Age needs attention because the older an individual gets, the worse the recovery will be. If the reticular activation system (RAS) in the brainstem remains intact or undisturbed, patients with head injury will remain fully conscious. Conclusion: It is expected that this research results can be additional information for hospitals to improve the quality of nursing care for patients with head injury, especially monitoring the consciousness level. The results of this research are also expected can be a source of information and reference in nursing education institutions regarding the overview of the consciousness level of patients with head injury using GCS. Further research is needed to compare the accuracy of the consciousness level assessment using GCS and other alternative scales such as the Full Outline of Unresponsiveness (FOUR) or the Comprehensive Level of Consciousness Scale (CLOCS).Keywords: Head injury, GCS, consciousness level.